Optimal Carbon Pricing and Income Taxation Without Commitment - Alex Schmitt (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2018)
At what rate should a government price carbon emissions? This paper analyzes optimal carbon pricing while taking into account interactions with the taxation of labor and capital income. In an otherwise standard climate-economy model, the policy maker has to resort to a distortionary tax on labor and capital income, and is unable to commit to future policies. I show that the optimal time-consistent carbon price is in general not at its Pigouvian level, that is, at the level of marginal damages induced by climate change. This is due to the presence of costs and benefits of emitting carbon that only materialize in the presence of income taxes. Quantitatively, I find that in a standard calibration of the model, this tax-interaction effect accounts for deviation of the optimal tax from the level of marginal climate damages in the ballpark of 10%, due to the second-best effects partially offsetting each other. Compared to a setting with lump-sum income taxes, I observe a smaller optimal carbon price without commitment, with the average differences over time amounting to 14%.
Keywords: E61; E62; H21; H23; Q54; 330; Climate-economy modeling; carbon tax; optimal income taxation